Pengaruh Sistem Pelayanan Kependudukan Klampid New Generation Terhadap Peningkatan Pelayanan Publik Di Kecamatan Sawahan Kota Surabaya - Pratama Harry Bowo (Pusat Riset dan Inovasi Nasional, 2025)
This study aims to investigate the effect of the Klampid New Generation Application System on improving public services in Sawahan Subdistrict, Surabaya City. In the era of digitalization and technological transformation, application systems are one of the tools used to improve the efficiency and effectiveness of public services. Klampid New Generation is one of the application systems introduced to facilitate interaction between local governments and communities in order to improve services. The research method used used a quantitative questionnaire distributed to respondents regarding the use of the Klampid New Generation Application System and their perceptions of public services.